2009
DOI: 10.1063/1.3152437
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation on bubble detachment from submerged orifice in quiescent liquid under normal and reduced gravity

Abstract: Investigation on two-phase flow in small diameter non-circular channels under low and normal gravity AIP Conf.In this work numerical simulations have been carried out to study the problem of dynamic air bubble formation from a submerged orifice in quiescent liquid, under constant inflow condition, at normal and reduced gravity levels. A coupled level-set and volume-of-fluid method is used to simulate the bubble formation, bubble detachment, and the bubble rise above the orifice. For the described study, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Some work has been performed on mathematically predicting adiabatic bubble formation and include the use of the boundary integral method [17][18][19][20][21], the Lattice-Boltzmann method [22] and numerical integration of the capillary equation [23][24][25]. More recently, CFD simulations have been performed to study various aspects of adiabatic bubble formation [26][27][28][29][30][31][32][33] on submerged orifices and nozzles and the results show that this is a very promising avenue for research in this branch of physics.…”
Section: Introductionmentioning
confidence: 99%
“…Some work has been performed on mathematically predicting adiabatic bubble formation and include the use of the boundary integral method [17][18][19][20][21], the Lattice-Boltzmann method [22] and numerical integration of the capillary equation [23][24][25]. More recently, CFD simulations have been performed to study various aspects of adiabatic bubble formation [26][27][28][29][30][31][32][33] on submerged orifices and nozzles and the results show that this is a very promising avenue for research in this branch of physics.…”
Section: Introductionmentioning
confidence: 99%
“…Gordillo et al 52 reported numerical results of the characteristics of the minimum neck radius of the bubbles with time at high Reynolds numbers. Gerlach et al, 55 Buwa et al, 56 and Chakraborty et al 57 used the CLSVOF method to evaluate the bubble formation process at a single submerged orifice under low and high gas flow rates. In their work, the effects of the orifice diameter, 56 gravity, 57 and gas flow rates on the period-1 and period-2 bubbling regimes and their transition characteristics 55,56 were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Gerlach et al, 55 Buwa et al, 56 and Chakraborty et al 57 used the CLSVOF method to evaluate the bubble formation process at a single submerged orifice under low and high gas flow rates. In their work, the effects of the orifice diameter, 56 gravity, 57 and gas flow rates on the period-1 and period-2 bubbling regimes and their transition characteristics 55,56 were reported. To the best of the authors' knowledge, there has been no numerical study to investigate the dynamics of bubble formation and rising in a high-density liquid metal as one of the fluids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ease the calculations, numerical treatments of the problem often assume the bubble to be a sphere 13,14 or a truncated spherical segment, 15,16 or use other simplifying assumptions depending on the aim of the particular investigation. For example, in Refs.…”
Section: Introductionmentioning
confidence: 99%